Intervensi Rendahnya Cakupan Keluarga Berencana dengan Penyuluhan, Pembagian Brosur dan Pemasangan Spanduk - Sri Wahyuni; Martalena Br. S. Kembaren; David Siagian (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
Family planning is an increase in community awareness and participation through maturing the age of marriage, birth control, fostering family resilience, increasing family welfare to create a small, happy and prosperous family. Belawan II Village, Medan Belawan District, where most of the population lives as fishermen and laborers with a medium economic level, very dense population settlements, surrounded by wide beaches and lack of public awareness and knowledge about family planning to make family planning coverage in the village. This is still low, namely 40% of the total couples of childbearing age. From the results of the observations of the puskesmas in accordance with the indicators of healthy families, it was found that the family index value based on families participating in the family planning program was 33%. The intervention carried out to overcome this problem was to provide counseling about family planning, distribution of posters and installation of banners as a form of family planning campaign. Counseling was carried out to 73 heads of families. All the families who attended were very enthusiastic about participating in the counseling. The distribution of posters and banners is done to serve as a reminder to the public about the importance of family planning. The results of the evaluation of this activity indicate a change in public knowledge about family planning.